Narrative as social action: a narratological approach to story, discourse and positioning in political storytelling. Issue 4 (3rd July 2020) - Björninen, Samuli; Hatavara, Mari; Mäkelä, Maria
ABSTRACT: Many sociologists have called for analytical rigor in the study of narrative while maintaining that narrative should be viewed as a form of social action. We argue that the narratological story-discourse distinction together with positioning theory provides a theoretical basis for such rigor. In narratology, story denotes the events in the world of the narrative, while discourse is the text that communicates them. This distinction helps us see how storytellers take positions on three levels: the story, the communicative (inter)action ( discourse ), and the level of norms . The third level derives from Michael Bamberg's positioning theory, which offers a frame of understanding the social situatedness of storytelling. Narratological analysis of linguistically discernible voices on the story and discourse levels offers methodological refinements for analysis, finally allowing for a focus on positioning on the third, normative level. The theoretical and methodological arguments are illustrated through analyses of Finnish politicians' stories.